1969
DOI: 10.1172/jci106178
|View full text |Cite
|
Sign up to set email alerts
|

Lipid metabolism in human platelets

Abstract: A B S T R A C T Washed human platelets were incubated with radioactive glycerol; the platelets were able to synthesize de novo the major phosphoglycerides including phosphatidic acid, phosphatidylinositol, phosphatidyl choline, phosphatidyl ethanolamine, and phosphatidyl serine. The specific activities of the phosphoglycerides obtained after glycerol incorporation indicate that phosphatidic acid, phosphatidylinositol, and phosphatidyl choline are metabolically active relative to phosphatidyl ethanolamine and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0
2

Year Published

1971
1971
1989
1989

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(16 citation statements)
references
References 25 publications
2
12
0
2
Order By: Relevance
“…The composition of the phospholipid fraction is given in Table II. Our data agree reasonably well with data in the literature (31)(32)(33)(34)(35)(36)(37)(38)(39). A small amount of phosphatidylinositol was detectable but was not quantified.…”
Section: Introductionsupporting
confidence: 91%
See 1 more Smart Citation
“…The composition of the phospholipid fraction is given in Table II. Our data agree reasonably well with data in the literature (31)(32)(33)(34)(35)(36)(37)(38)(39). A small amount of phosphatidylinositol was detectable but was not quantified.…”
Section: Introductionsupporting
confidence: 91%
“…Immunoelectrophoresis was carried out as described by Scheidegger (27) Phospholipids. In good accordance with data of others (30,31), the platelets were found to contain 10.0-13.9 ug lipid phosphorus/109 platelets. The composition of the phospholipid fraction is given in Table II.…”
Section: Introductionsupporting
confidence: 91%
“…Previous work done in our laboratory (2) has shown that thrombin causes a 7-fold increase in the rate of incorporation of glycerol into phosphatidyl serine in the platelet membrane. This burst in the rate of lipid synthesis is maximal within 2 min of the addition of thrombin and such synthesis returns to the pre-thrombin rate by 20 (8).…”
mentioning
confidence: 76%
“…Platelets are anucleate circulating particles, with a diameter of [2][3][4] Mum in man, which function in hemostasis. These "cells" are metabolically active and catalyze the formation of fatty acids, phospholipids, glycogen, and even protein (1).…”
mentioning
confidence: 99%
“…Although considerable information has been accumulated regarding the biochemistry and physiology of platelet-plug formation (1)(2)(3)(4)(5)(6)(7), little is known about initiation of platelet plug formation, namely platelet adhesion. Early work, employing light microscopy, (8)(9)(10) had suggested that platelets adhered to traumatized mesenteric fibers which were of "collagen" nature.…”
Section: Introductionmentioning
confidence: 99%